2019
DOI: 10.1021/acs.iecr.8b06455
|View full text |Cite
|
Sign up to set email alerts
|

Trace Zinc-Preload for Enhancement of Uranium Adsorption Performance and Antifouling Property of AO-Functionalized UHMWPE Fiber

Abstract: Varieties of microorganisms in seawater exhibit negative effects on the performance of adsorbents in uranium uptake from seawater. In this study, a novel adsorbent with excellent antifouling property was synthesized by preloading trace zinc ions in amidoxime (AO)-functionalized UHMWPE fiber. The zinc ions preloaded onto the adsorbents not only gave antimicrobial properties to Aspergillus niger, Escherichia coli, Bacillus subtilis, and Vibrio alginolyticus but also enhanced the adsorption capacity of the adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…To understand the practical application of the obtained adsorbent in seawater, Jute-TMC-PAO (10 mg) was employed to [42][43][44][45][46][47][48][49][50] extract uranium in simulated natural seawater using the apparatus shown in Fig. S12 (ESI †), and the model diagram is described in Fig.…”
Section: Adsorption Performance In Simulated Natural Seawatermentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the practical application of the obtained adsorbent in seawater, Jute-TMC-PAO (10 mg) was employed to [42][43][44][45][46][47][48][49][50] extract uranium in simulated natural seawater using the apparatus shown in Fig. S12 (ESI †), and the model diagram is described in Fig.…”
Section: Adsorption Performance In Simulated Natural Seawatermentioning
confidence: 99%
“…Uranium adsorption result in simulated natural seawater for 14 days (B), inset: Color of the Jute-TMC-PAO fabric before and after uranium adsorption. Comparison of the uranium adsorption amount and adsorption rate of certain representative fibrous adsorbents in real seawater (C) [42][43][44][45][46][47][48][49][50].…”
mentioning
confidence: 99%
“…Grafting amidoxime on C-based material improves the selectivity and affinity for U electrosorption. 31,34,35 The current mode during the electrosorption process also proved important for UO 2 2+ removal and recovery. It was reported that halfwave rectified alternating current electrochemical (HW-ACE) can efficiently extract UO 2 2+ from seawater with high UO 2 2+ selectivity using CF as electrode.…”
Section: +mentioning
confidence: 99%
“…prepared amidoxime‐grafted functional magnetic chitosan (AO‐AHC) that was found to be more selective for U (VI) than zirconium(Zr) (IV) at pH 4; the selectivity to U (VI) was high especially in ore leachates containing aluminum [Al (III)], iron [Fe (III)] and calcium [Ca (II)] ions. Ahmad et al 33 . found desirable selectivity and recyclability using an amidoxime‐modified porous organic polymer flower‐like structure (POP‐AOF) for U (VI) uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In marine environments, there are numerous microorganisms as well as natural organic matter, which can affect the adsorption performance of adsorbents. [52][53][54] Both AO-Imp(250) ber and AO ber exhibited lower adsorption capacity of uranium in the marine environment than in the laboratory. However, the adsorption capacity ratio of uranium to vanadium (U/V) increased from 0.70 to 0.94.…”
Section: Adsorption Selectivity In Natural Seawatermentioning
confidence: 99%